3D Printing technologies for drug delivery: a review. (2nd July 2016) - Prasad, Leena Kumari; Smyth, Hugh
Abstract: With the FDA approval of the first 3D printed tablet, Spritam®, there is now precedence set for the utilization of 3D printing for the preparation of drug delivery systems. The capabilities for dispensing low volumes with accuracy, precise spatial control and layer-by-layer assembly allow for the preparation of complex compositions and geometries. The high degree of flexibility and control with 3D printing enables the preparation of dosage forms with multiple active pharmaceutical ingredients with complex and tailored release profiles. A unique opportunity for this technology for the preparation of personalized doses to address individual patient needs. This review will highlight the 3D printing technologies being utilized for the fabrication of drug delivery systems, as well as the formulation and processing parameters for consideration. This article will also summarize the range of dosage forms that have been prepared using these technologies, specifically over the last 10 years.